2014
DOI: 10.1039/c3cy01011b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the selectivity of a supported gold catalyst in solvent- and radical initiator-free aerobic oxidation of cyclohexene

Abstract: The selectivity of supported gold catalysts in solvent- and radical initiator-free aerobic oxidation of cyclohexene was tuned by either WO3 or MIL-101.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
0
29
1
Order By: Relevance
“…This then limits possible yield to cyclohexane diol, a key intermediate in the formation of adipic acid. An adapted mechanism from the paper by Ovoshchnikov et al is shown in Scheme 3 for the formation of cyclohexane diol with the addition of water [31]. The results in Table 2 demonstrate the importance of water in the formation of cyclohexane diol, and therefore any process that achieves high selectivity to the epoxide would be limited because of the lack of in situ water formed via dehydration of the hydroperoxyl intermediate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This then limits possible yield to cyclohexane diol, a key intermediate in the formation of adipic acid. An adapted mechanism from the paper by Ovoshchnikov et al is shown in Scheme 3 for the formation of cyclohexane diol with the addition of water [31]. The results in Table 2 demonstrate the importance of water in the formation of cyclohexane diol, and therefore any process that achieves high selectivity to the epoxide would be limited because of the lack of in situ water formed via dehydration of the hydroperoxyl intermediate.…”
Section: Discussionmentioning
confidence: 89%
“…This large discrepancy between sol immobilisation and impregnation selectivity is likely linked to their activity, as the small Scheme 3. Adapted reaction scheme from Ovoschnikov et al for effect of additional water [31].…”
Section: Discussionmentioning
confidence: 99%
“…a bulk-like Au signal in XPS) and a distinct surface plasmon resonance band. [25][26] Peaks with intermediate binding energies (84 -84.5 eV) can be attributed to the small aggregates of clusters. It is also important to note that agglomeration of clusters affects the intensity of the Au signal.…”
Section: Effects Of Pre-and Post-deposition Treatment On Au Xpsmentioning
confidence: 97%
“…The fundamental study reported herein is therefore intended to act as a foundation for further studies on the applications of these materials. [25][26][27] In the proceeding sections we present X-ray photoelectron spectroscopy (XPS) measurements of the gold core, the triphenylphosphine periphery, and the titanium dioxide support respectively. Following this, we present results of the UV-vis DRS spectroscopy investigations of these (and related) materials, which support the conclusions obtained from XPS data.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] For example, using silica or manganese oxide supported gold catalysts, selectivity for production of epoxide (i.e., cyclohexene oxide) is generally lower than 10% when molecular oxygen was used. 31,32 In order to improve the selectivity for production of cyclohexene oxide, gold nanoclusters (i.e., Au 9 and Au 101 ) were anchored onto WO 3 nanoparticles 35 ; the selectivity for production of cyclohexene oxide on Au 101 /WO 3 catalyst was improved largely to 35% comparing to 7% of Au 101 /SiO 2 catalyst when molecular oxygen or peroxide is used as the oxidant. 35 This difference suggests the promotion effect of the support, WO 3 on catalytic selectivity of cyclohexene oxide.…”
Section: Introductionmentioning
confidence: 99%